Factors Associated with Spontaneous Clearance of Hepatitis C Virus among Illicit Drug Users - Jason Grebely; Jesse D Raffa; Calvin Lai; Mel Krajden; Brian Conway; Mark W Tyndall (Canadian Journal of Gastroenterology, 2007)
BACKGROUND: Spontaneous clearance of hepatitis C virus (HCV) occurs in approximately 25% of individuals.